Analysis of the Effect of Capacitor Installation and Rectifier Circuit on the Reciprocating Load of a Single-Phase AC Generator - Adam Maulana (Journal of Marine Electrical and Electronic Technology, 2023)
The role of rectifier circuits in electronic technology has long been known and often discussed. However, in its application, there is still a lot of potential that can be modified from this rectifier series so that the output produced becomes more optimal and can be applied in daily use. The rectifier circuit serves to convert alternating current (AC) into direct current (DC) [3]. Generators are also a component that is popularly used as an object of experimentation and research in the field of power electronics. A single-phase AC generator consists of a stator that generates electric current, a rotor to create a magnetic field, and an air gap between the stator and rotor [1]. With this construction, this generator is able to convert mechanical energy into electrical energy which produces alternating voltage (AC). This study discusses the analysis of the influence of uncontrolled capacitor installations and half-wave rectifier circuits on recisive loads in single-phase AC generators. In the experiments conducted, the installation of capacitors had a significant impact on the output waveform produced by the rectifier circuit. The sinusoidal waves generated by the single-phase AC generator will be straightened by the diode, and the installation of capacitors in parallel with the recisive load can reduce the noise generated in the output waves, so that the output is closer to the properties of pure direct current (DC) [2]. These findings provide a new understanding of the application of capacitors in improving the quality of power output generated by single-phase AC generators, which has the potential for further applications in the field of small electric power systems.